PENINGKATAN PRODUKSI ULAT JERMAN MELALUI KOMBINASI PEMANFAATAN LIMBAH SAYURAN PASAR PADA FORMULASI MEDIA PAKAN YANG BERBEDA - Erik Priyo Santoso; Akhadiyah Afrila; Eka Fitasari (BUANA SAINS, 2017)
Waste vegetable of traditional market provided very abundant and rarely used. German mealworm known as giant meal worms are the larvae of insects named Zhopobas morio parent has a size larger than the hongkong mealworm. The purpose of this study was to determine the application of vegetable waste in feed media of German mealworm which has a different nutrient content. This experiment using a completely randomized design (CRD) factorial design with treatment G1P1 (GE 4000 kcal / kg, PK 10%), G1P2 (GE 4000 kcal / kg, PK 12%), G1P3 (GE 4000 kcal / kg, PK 14% ), G2P1 (GE 4500 kcal / kg, PK 10%), G2P2 (GE 4500 kcal / kg, PK 12%), G2P3 (GE 4500 kcal / kg, PK 14%), G3P1 (GE 5000 kcal / kg PK 10 %) G3P2 (GE 5000 kcal / kg PK 12%), G3P3 (GE 5000 kcal / kg PK 14%), each treatments replicated 3 times. The results of the research showed that the application of vegetable waste in german worm feed media is able to increase the use of feed concentrates containing gross energy and crude protein low. Vegetable waste treatment in feed media which containing gross energy of 4000 kcal / kg and 14% crude protein showing the highest value on dry matter feed intake, weight of the harvest, and worm weight gain.